Pengaruh Media Sosial (Instagram) dan Daya Tarik Pengunjung Terhadap Minat Berkunjung Ke City Light Jalan Tunjungan Surabaya - Putri Dwi Rahayu; Mei Putri Lestari; Utami Puji Lestari (STIKes Ibnu Sina Ajibarang, 2024)
This research was conducted of analyzing the influence of social media and visitor attraction on interest in visiting City Light Jalan Tunjungan Surabaya as a tourist attraction and marketing via Instagram as a medium on the interest of tourists or visitors to visit this tourist attraction. This research uses quantitative methods. The results of this research show that social media does not have a significant effect on interest in visiting City Light Jalan Tunjungan Surabaya. Meanwhile, attractiveness has a significant influence on interest in visiting City Light Jalan Tunjungan Surabaya.